A DNA sequence design for direct-proportional length-based DNA computing using DNA Sequence Generator - 238089 Wan Nazihah Wan Ibrahim; Wan Nazihah Wan Ibrahim, 1983-, author; Tri, Basuki Kurniawan, 1974-, author; Marzuki Khalid, author; Osamu Ono, author; Internatinol Conference on Innovative Computing Information and Control (2nd : 2007 : Kumamoto, Japan)i (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL